Evaluation of Antihypoxic Activities of Naringin and Naringenin in Asphyxia, Haemic and Circulatory Hypoxia Models in Mice - Amin Barani; Hossein Rezaee; Karimollah Dinee; Mohammad Ali Ebrahimzadeh (Journal of Mazandaran University of Medical Sciences, 2024)
Background and purpose: Hypoxia is a decrease in available oxygen reaching the tissues of the body which can lead to body function impairment. It is linked to the pathology of acute mountain sickness, cardiovascular disease, and stroke. Hypoxia causes oxidative stress involving the production of reactive oxygen species (ROS). Naringenin and naringin are widely found in Citrus spp. These compounds have many biological effects, potent antioxidant activities, and influential effects in ischemia/reperfusion. Nothing is found about the anti-hypoxic activities of these compounds. This study aimed to investigate the anti-hypoxia activities of these compounds in mice. Materials and methods: In this experimental study, the protective effects of these compounds at 5-20 mg/kg were evaluated against hypoxia-induced lethality in mice by three experimental models of hypoxia, i.e. asphyctic, haemic, and circulatory hypoxia.  The latencies for death for mice in minutes were recorded. All the experimental procedures were conducted by the NIH guidelines of the Laboratory Animal Care and Use. The Institutional Animal Ethical Committee of Mazandaran University of Medical Sciences also approved the experimental protocol. In the asphyctic hypoxic model, phenytoin (50 mg/kg, i.p.) and in the next two tests, propranolol (20 and 30 mg/kg, i.p.) were used as the positive controls. In all tests, Normal saline (0.5 ml, i.p.) was used as the negative control. Analysis of variance was performed followed by Newman-Keuls multiple comparisons (by GraphPad Prism 8) were used to determine the differences in means. Results: In the circulatory model, both compounds showed very good effects. The effects were completely dose-dependent. Naringin at a dose of 5 mg/kg increased the death time by approximately 7.3 minutes (P<0.01). Naringenin at 10 mg/kg significantly increased the death time by 3.2 minutes (P<0.01). These compounds in these doses showed a similar effect to propranolol, which was used as a positive control. In the haemic model, only naringin showed a very good and dose-dependent effect. These compounds at 5 mg/kg increased the survival time by about 4.5 minutes (P<0.01). Naringenin had no effect in this model even at a dose of 40 mg/kg. Naringin at 5 mg/kg and naringenin at 40 mg/kg showed a similar effect to propranolol. In the asphyctic model, both compounds showed great effects. Their effects were completely dose-dependent. Naringin at 5 mg/kg increased the time to death by 7.2 minutes (P<0.001). At the dose of 10 mg/kg, the death time was increased by 10 minutes and reached 29 minutes (P<0.0001). Naringenin at 5 mg/kg increased the survival time of mice by 4.2 minutes (P<0.05). At the dose of 10 mg/kg, the death time was increased by 10 minutes and reached 27 minutes (P<0.0001). Naringenin at 5 and naringenin at 10 mg/kg produced a similar effect to phenytoin, which was used as a positive control (P>0.05). Conclusion: According to the results of this study, it was found that Naringin has very good protective activities in all models. Naringenin was not effective in the haemic model. The result of this research can be responsible for cardiovascular effects and their good effects on ischemia/reperfusion.